2021
DOI: 10.1093/jas/skab094
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of beta-ligands used in cattle production: structures, safety, and biological effects

Abstract: Technologies that increase the efficiency and sustainability of food animal production to provide meat for a growing population are necessary and must be used in a manner consistent with good veterinary practices, approved labeled use, and environmental stewardship. Compounds that bind to beta-adrenergic receptors (β-AR), termed beta-adrenergic receptor ligands (β-ligands), are one such technology and have been in use globally for many years. Though all β-ligands share some similarities in structure and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…2 These observations are presumably reason for some β-agonists being used or misused as growth promoters in the farming industry. 1 Representatives of this drug class are clenbuterol, cimaterol, salbutamol, ractopamine, and zilpaterol. Zilpaterol is a synthetic β-adrenoreceptor agonist with an enantiomeric structure (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 These observations are presumably reason for some β-agonists being used or misused as growth promoters in the farming industry. 1 Representatives of this drug class are clenbuterol, cimaterol, salbutamol, ractopamine, and zilpaterol. Zilpaterol is a synthetic β-adrenoreceptor agonist with an enantiomeric structure (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Beta-adrenoreceptor agonists (β-agonists) are used as bronchodilators to treat pulmonary diseases in humans and animals. 1 Since the 1980s, various studies have indicated anabolic/growth-promoting effects when β-agonists are used at higher doses, leading to increased muscle mass and reduced body fat percentage. 2 These observations are presumably reason for some β-agonists being used or misused as growth promoters in the farming industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUB is a selective β-modulator ( SβM ) which selectively binds to the β-adrenergic receptor and has agonistic properties at the β 3 -receptor subtype and antagonistic properties at β 1 - and β 2 -receptor subtypes in cattle ( Dilger et al, 2021 ), and as such, is classified by the Center of Veterinary Medicine ( CVM ) as a ‘beta-adrenergic agonist/antagonist’ ( FDA, 2018 ). This pharmacodynamic profile differentiates LUB from the β-ligands historically used in livestock species, as their apparent mode of action is predominately through agonistic behavior at either the β 1 - or the β 2 -receptor subtype.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, LUB selectively binds to β-adrenergic receptors (binding affinity observed at ≤0.5 nM) and has low binding affinity for non-β-adrenergic receptors (i.e., no affinity observed at >300 nM for muscarinic, 5-HT 2 , dopamine D 1 and D 2 , α 1 - and α 2 -adrenergic, benzodiazepine, histamine H 1 , or GABA A receptors; FDA, 2018 ). Because of its selectivity and modulating characteristics, LUB can simply and accurately be described as a selective β-modulator, SβM ( Dilger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%